Experimental Vibration Analysis for Civil Structures Testing, Sensing, Monitoring, and Control - Conte, Joel P.; Astroza, Rodrigo; Benzoni, Gianmario; Feltrin, Glauco; Loh, Kenneth J.; Moaveni, Babak (Lecture Notes in Civil Engineering, 2018)
This edited volume presents selected contributions from the International Conference on Experimental Vibration Analysis of Civil Engineering Structures held in San Diego, California in 2017 (EVACES2017). The event brought together engineers, scientists, researchers, and practitioners, providing a forum for discussing and disseminating the latest developments and achievements in all major aspects of dynamic testing for civil engineering structures, including instrumentation, sources of excitation, data analysis, system identification, monitoring and condition assessment, in-situ and laboratory experiments, codes and standards, and vibration mitigation.